Cancer-Associated Substitutions in RNA Recognition Motifs of PUF60 and U2AF65 Reveal Residues Required for Correct Folding and 3' Splice-Site Selection - Kralovicova, Jana; Borovska, Ivana; Kubickova, Monika; Lukavsky, Peter J; Vorechovsky, Igor (Cancers, 2020)
U2AF65 (U2AF2) and PUF60 (PUF60) are splicing factors important for recruitment of the U2 small nuclear ribonucleoprotein to lariat branch points and selection of 3' splice sites (3'ss). Both proteins preferentially bind uridine-rich sequences upstream of 3'ss via their RNA recognition motifs (RRMs). Here, we examined 36 RRM substitutions reported in cancer patients to identify variants that alter 3'ss selection, RNA binding and protein properties. Employing PUF60- and U2AF65-dependent 3'ss previously identified by RNA-seq of depleted cells, we found that 43% (10/23) and 15% (2/13) of independent RRM mutations in U2AF65 and PUF60, respectively, conferred splicing defects. At least three RRM mutations increased skipping of internal U2AF2 (~9%, 2/23) or PUF60 (~8%, 1/13) exons, indicating that cancer-associated RRM mutations can have both cis- and trans-acting effects on splicing. We also report residues required for correct folding/stability of each protein and map functional RRM substitutions on to existing high-resolution structures of U2AF65 and PUF60. These results identify new RRM residues critical for 3'ss selection and provide relatively simple tools to detect clonal RRM mutations that enhance the mRNA isoform diversity.
Keywords: pre-mRNA splicing; leukemia; cancer; mRNA; differential scanning fluorimetry; lariat branch point; SF3B4; PUF60; gel shift assay; 3′ splice site; Functional genomics; driver mutation; U2AF2; exon inclusion